2020
DOI: 10.3332/ecancer.2020.1089
|View full text |Cite
|
Sign up to set email alerts
|

Early molecular response in East African Philadelphia chromosome-positive chronic myeloid leukaemia patients treated with Imatinib and barriers to access treatment

Abstract: Background Data about haematologic malignancies from Tanzania are sparse. African studies show that chronic myeloid leukaemia (CML) is the most common leukaemia, and registry data display a lower mean age at diagnosis. Prognosis is generally good with tyrosine kinase inhibitors, but the molecular response of Imatinib treatment has never been studied in East Africa, and the outcome remains unknown. This study assessed the early molecular response (MR) as a predictor for long-term outcome and barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The mechanisms of action and toxicity of the medications used to treat CML differ. In a study conducted by Oliver Henke et al [ 18 ]: it was observed that Imatinib’s utilization in the management of CML radically altered the way this disease was addressed and spurred the advent of additional potent targeted protein kinase inhibitors. FDA-approved drugs for initial therapy comprise imatinib as an initial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of action and toxicity of the medications used to treat CML differ. In a study conducted by Oliver Henke et al [ 18 ]: it was observed that Imatinib’s utilization in the management of CML radically altered the way this disease was addressed and spurred the advent of additional potent targeted protein kinase inhibitors. FDA-approved drugs for initial therapy comprise imatinib as an initial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The median age at diagnosis was estimated to be 60 years in western countries, but the age at diagnosis in Africa and Asia was about ten years younger. 19 Besides, CML is more common in males than in females with the male/female ratio of 1.2-1.7. However, to the best of our knowledge, no studies have characterized the distribution and burden of CML worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In Sudan, CML incidence has increased considerably in recent years. It is the most common type of leukemia in age groups above 15 years; however, of all leukemia types, it is the second most common malignancy [ 6 , 7 ]. A recent study reported that diet and physical activities are both factors contributing to the rise of cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%